Relationships between Chapters IV and V of the Preliminary Title of the Civil Code in the application of Civil law of the autonomous communities - Álvarez Rubio, Juan José (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The complex interaction between both Chapters (IV and V) of the Preliminary Title of the Civil Code allows us to appreciate the existence of a whole series of distortions in its application in the face of a long list of supervening issues, not foreseen by the legislator and that are in need of a new regulatory development in order to overcome regulatory gaps, as well as update conflictive solutions and finally be able to provide the system of interregional law with a hitherto non-existent internal coherence. Our Spanish legal system actually lacks a true system of Interregional Law. And this unique and increasingly accentuated internal regulatory plurality is also the object of growing attention and regulatory regulation at the European level and in the conventional/international regulatory block. It is therefore urgent to undertake the reform of this sector of our legal system, keeping in mind a perspective based on the obligatory hybridization of three dimensions (constitutional, legal-private, European and internal) in order to be able to base the establishment of a coherent set of rules that provide legal security to the system.